1
$\begingroup$

I want to show that:

Given $f,g \in C^\infty(M)$ defined in a differential manifold of dimension $n$ and $a \in M$, we have $$(dfg)_a=f(a)(dg)_a+g(a)(df)_a,$$

using the following proposition:

Let $M$ be a $n$-dimensional manifold.

Let $(U,\varphi)$ be a coordinate chart around $a$ with coordinates $x_1,\ldots,x_n$.

Then, if $f \in C^\infty(M)$ and in the coordinate chart $f \varphi^{-1} = \phi(x_1,\ldots,x_n)$, we have $$(df)_a=\sum_{i=1}^n \frac{\partial \phi}{\partial x_i}(\varphi(a))(dx_i)_a$$

My atempt: $$f(a)(dg)_a + g(a)(df)_a = f(a)\sum_{i=1}^n \frac{\partial \phi_2}{\partial x_i}(\varphi(a))(dx_i)_a + g(a) \sum_{i=1}^n \frac{\partial \phi_1}{\partial x_i}(\varphi(a))(dx_i)_a$$

So, $$f(a)(dg)_a + g(a)(df)_a = \sum_{i=1}^n [f(a)\frac{\partial \phi_2}{\partial x_i}(\varphi(a)) + \frac{\partial \phi_1}{\partial x_i}(\varphi(a))](dx_i)_a$$

Now confusion begins, I can't proceed but I know that:

  1. $f\varphi^{-1}=\phi_1(x_1,\ldots,x_n)$

  2. $g\varphi^{-1}=\phi_2(x_1,\ldots,x_n)$

I would greatly appreciate it if you give me some hint or solution.

$\endgroup$
  • $\begingroup$ Oh, I'm seeing that $fg=(\phi_1 \circ \varphi)(\phi_2 \circ \varphi) = \phi_1 \phi_2 \circ \varphi$ $\endgroup$ – Leafar Mar 7 '15 at 19:52
1
$\begingroup$

We have $$(dfg)_a = \sum_{i=1}^n \frac{\partial(\phi_1 \phi_2)}{\partial x_i}(\varphi(a))(dx_i)_a,$$

so $$(dfg)_a = \sum_{i=1}^n [\frac{\partial\phi_1}{\partial x_i}(\varphi(a))\phi_2(\varphi(a)) + \phi_1(\varphi(a))\frac{\partial \phi_2}{\partial x_i}(\varphi(a))](dx_i)_a,$$

then $$(dfg)_a = \sum_{i=1}^n [\frac{\partial\phi_1}{\partial x_i}(\varphi(a))g(a) + f(a)\frac{\partial \phi_2}{\partial x_i}(\varphi(a))](dx_i)_a,$$

which matches the attempt.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.